2012
DOI: 10.2478/s11658-012-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Sulphamoylated estradiol analogue induces antiproliferative activity and apoptosis in breast cell lines

Abstract: Abstract:Research into potential anticancer agents has shown that 2-methoxyestradiol exerts antiproliferative activity in vitro and in vivo in an estrogen receptor-independent manner. Due to its limited biological accessibility and rapid metabolic degradation, several new analogues have been developed in recent years. This study investigated the in vitro effects of a novel in silicodesigned compound (C16) in an estrogen receptor-positive breast adenocarcinoma epithelial cell line (MCF-7), an estrogen receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 15 publications
5
33
0
Order By: Relevance
“…Cells that divided in the presence of the C9+DCA treatment proceeded from being arrested at the mitotic phase to forming multiple micronuclei and apoptotic bodies. Other studies recently conducted also showed similar results where a sulphamoylated antimitotic compound-treated MCF-7, and/or MDA-MB-231 or esophageal carcinoma cells (SNO) cells showed a decrease in cell density along with morphological indicators of apoptosis [8,28,62]. Distorted cell shape, high density of digit-like apical microvilli, formations of vacuoles, lysosomes and apoptotic bodies, heterochromatin, as well as fragmented DNA were detected in both cell lines by means of transmission electron microscopy.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Cells that divided in the presence of the C9+DCA treatment proceeded from being arrested at the mitotic phase to forming multiple micronuclei and apoptotic bodies. Other studies recently conducted also showed similar results where a sulphamoylated antimitotic compound-treated MCF-7, and/or MDA-MB-231 or esophageal carcinoma cells (SNO) cells showed a decrease in cell density along with morphological indicators of apoptosis [8,28,62]. Distorted cell shape, high density of digit-like apical microvilli, formations of vacuoles, lysosomes and apoptotic bodies, heterochromatin, as well as fragmented DNA were detected in both cell lines by means of transmission electron microscopy.…”
Section: Discussionsupporting
confidence: 52%
“…Haematoxylin and eosin (H&E) stains were used to recognise various cytoplasmic and nuclear morphologic changes [27], as well as to determine the mitotic index [28]. MCF-7 and MCF-12A cells were seeded in 6-well plates at a density of 375 000 cells/3 ml medium/well on heat-sterilized cover slips.…”
Section: Methodsmentioning
confidence: 99%
“…PlasDIC is an improved polarization-optical transmitted light differential interference contrast method that allows linearly polarized light to be generated only after the objective [12,31,34]. PlasDIC provides high-quality imaging of cells in plastic cell culture vessels.…”
Section: Polarization-optical Differential Interference Contrast Micrmentioning
confidence: 99%
“…2-methoxyoestradiol (2ME) is an endogenous metabolite derived from 17β-estradiol (Fig. 1A) [7][8][9][10][11][12]. Research has shown that this compound has antiproliferative, antiangiogenic and pro-apoptotic characteristics in vitro and in vivo [3,[7][8][9][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation